Show that if y=2x-x² then $\displaystyle y*\frac{d^2y}{dx^2}-2*\frac{dy}{dx}+2y=4(x-1) $
Last edited by alibond07; Nov 29th 2009 at 01:21 PM.
Follow Math Help Forum on Facebook and Google+
Originally Posted by alibond07 Show that if y=2x-x² then $\displaystyle y*\frac{d^2y}{dx^2}-2*\frac{dy}{dx}+2y=4(x-1)$ Bear with me if it has been written wrong, still stying to get my head around LATEX . Is that what you mean?
Originally Posted by ANDS! Is that what you mean? Yes! , I'm actually quite jealous of your ability to do that :L,but anyway I havent got a clue with the maths :S Anyone know how to do it, i'm completely stumped.
I think you gotta learn basic derivatives techniques: The first derivative of y with respect to x is = 2-2x The second derivative of y with respect to x is = -2 Plug-in...
View Tag Cloud